Member's awareness on EPF withdrawal schemes / Aida Farrah Abdul Jalal - Abdul Jalal, Aida Farrah (Faculty of Business and Management, 2001)
The research has been conducted at Employees Provident Funds at Malacca. The EPF long-term aim is to ensure that every employee in Malaysia is covered under the EPF retirement schemes. This can be achieved by creating awareness among the members themselves of the importance of saving for old age. The research has discovered the level of awareness and knowledge among the EPF members on the withdrawal schemes. The conclusion of this study is the outcome from the survey analysis, finding and recommendations given by respondents. The researcher found that EPF's members still unaware and lacking in information on the EPF withdrawal schemes. The EPF in its effort to increase awareness and knowledge among the members has organized several promotional activities such as talks, seminars, education courses and distributing pamphlets to the members. The EPF has also used electronic media such as television and radio to create and to increase members the level of awareness on withdrawal schemes. Therefore, EPF needs to develop new promotional strategy in term of promotional tools, advertising media and internal strategy by maintaining good relationship with members. EPF also needs to improve the existing strategies in order to increase members' awareness.